OPTIMALISASI VISUAL BRANDING PRODUK WIRAUSAHA DI RSCA MAKASSAR MELALUI PELATIHAN DESAIN KEMASAN BERBASIS APLIKASI DIGITAL - Muhiddin Palennari; Erona Wafaretta; Christina Aryanti Pada Soa; Amaliah Amriani Amran Saru; Muhammad Syaiful Akbar; Diantri Utari; Muh. Ashabul Kahfi; Alni Delfianti U; Reski Sri Mulyani; Sazkia Annisa (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to improve santri at RSCAS Makassar's understanding and skills in developing product packaging through the use of digital design applications. The initial problem identified was the use of packaging that was still simple and not optimal in presenting visual branding. The activity was implemented using a participatory learning and experiential learning approach involving 10 participants through the stages of preparation, training, and evaluation. The training focused on understanding the strategic role of packaging in marketing, the development of visual identity, and hands-on practice using the Canva application. The results showed an improvement in participants’ conceptual understanding of packaging design, which enhances participants’ digital literacy, creativity, and independence in developing packaging designs. Overall, this activity contributes to strengthening visual branding and improving the competitiveness of santri entrepreneurial products